Evaluation of anti-inflammatory potential of the leaves of Wendlandia heynei (Schult.) Santapau & Merchant in Sprague Dawley rat. (28th June 2019) - Maryam, Sonia; Khan, Muhammad Rashid; Shah, Sayed Afzal; Zahra, Zartash; Batool, Riffat; Zai, Jawaid Ahmed
Abstract: Ethnopharmacological relevance: The leaves of W. heynei (family: Rubiaceae) are used by the folklore in swelling, wounds and body aches. In this study anti-inflammatory potential of W. heynei leaves has been evaluated during in vitro studies and in rat. Methods: Methanol extract of the leaves of W. heynei (WHLM) and its fractions; n-hexane (WHLH), chloroform (WHLC), ethyl acetate (WHLE), n-butanol (WHLB) and residual soluble aqueous (WHLA) were screened for phytochemical analysis and several active constituents (alkaloids, flavonoids, saponins, tannins, terpenoids, β-carotene and lycopene) were also quantified. Heat induced albumin denaturation assay and in vitro cell cultures was carried out for in vitro anti-inflammatory activity, while various in vivo assays like TPA induced ear edema, croton oil induced anus edema, formalin and carrageenan-induced hind paw edema was investigated in Sprague-Dawley rats. Alterations on levels of tumor necrosis factor (TNF-α), Interleukin-1β (IL-1β), IL-6 and prostaglandins (PGE2 ) induced with WHLE was studied in serum after carrageenan induced paw edema in rat. Meanwhile, the dose dependent WHLE inhibition of NFκB pathway via regulation of the phosphorylation of IKKs, IκBα, and p65 subunit was studied in LPS-induced rat peritoneal macrophages. On account of marked anti-inflammatory activity of WHLE its bioactive components were analyzed by HPLC-DAD analysis. Results: The phytochemical analysis yielded alkaloids, saponins, tannins, coumarins, glycosides, quinones and vitamin C in WHLM and in all fractions. Fraction (WHLE) was enriched with alkaloids (20.20 ± 2.5%), flavonoids (25.26 ± 2.11%) and tannins (307.2 ± 2.03 mg of GAE/g of extract), while terpenoids (21.60 ± 1.65%) were the major constituents of WHLH. Ethyl acetate fraction convincingly protected heat induced albumin denaturation. WHLE exhibited highest edema inhibition in models of TPA-induced ear edema (74.51 ± 2.05) and croton oil-induced anal edema (75.38 ± 2.83). The pretreatment with WHLE significantly (p < 0.05) reduced the paw edema with formalin (78.99 ± 2.26%) assessed after 6 h and in carrageenan (75.71 ± 4.46%) was detected after 4 h. Level of anti-inflammatory markers; IL-1β, IL-6, TNF-α and PGE2 in carrageenan induced paw edema in serum of rat was significantly (p < 0.001) decreased with WHLE pretreatment to rat. WHLE significantly inhibited the NFκB by reducing the phosphorylation of IKKs, IκBα, and p65 subunit in LPS-induced inflammation in rat peritoneal macrophages. HPLC-DAD analysis of WHLE indicated the presence of rutin, gallic acid, catechin, caffeic acid and myricetin. Conclusions: It is concluded that WHLM fractions have marked anti-inflammatory activity and this study endorsed the folklore use of W. heynei leaves for swelling related disorders. Graphical abstract: Image 1